Energy and Covid 19 : Analysis of the Impact on the Global Energy Matrix - Luiz Antonio Ferrari (Brazilian Journal of Radiation Sciences)
Pandemics reverberated their times, changing social and economic contexts, prompting, and redirecting changes in social ties, business, and education, restructuring the world that generated them. In this context, this study aims to assess the impact of the COVID-19 pandemic on the global energy matrix, supported by an analysis of consumption, demand, and GDP from January 2019 to June 2021. The energy balance showed variations in this period, with impacts on the environment. We will assess whether the changes will be lasting.